The Colonial Present in Ben Fountain’s Billy Lynn's Long Halftime Walk - M Alosman, M Ikbal (Dirasat: Human and Social Sciences, 2024)
Objectives: The objectives of this study are to explore the colonial techniques and effects used in the novel, Billy Lynn's Long Halftime Walk (2012) by Ben Fountain. The colonial present refers to the active state of colonization and its temporal existence in the present time. Methods: The novel is analyzed in two sections: the first section, "Colonial Justifications," examines the means employed in the novel to reinforce the colonial perspective of Iraq and its people. The second section, "Colonial Innocence," discusses how the negative colonial impact on the local population is erased throughout the narrative and how this erasure serves the comprehensive colonial argument. Results: Although Ben Fountain's novel mocks the war on Iraq and all the accompanying pro-war rhetoric, it still presents a colonial representation of Iraq and its people. Iraq is portrayed as a desert waiting for the West to come and make it flourish and develop. The Iraqis are depicted as in dire need of Western intervention to join the civilized world and interact with advanced nations. Conclusions: Colonial concepts persist in the novel, and the negative colonial repercussions on both the land and the people of Iraq are overlooked.